2018
DOI: 10.1093/jxb/ery188
|View full text |Cite
|
Sign up to set email alerts
|

Leaf hydraulic vulnerability triggers the decline in stomatal and mesophyll conductance during drought in rice

Abstract: Leaf hydraulic conductance plays a role in stomatal closure during soil drought, and reduction in CO2 diffusion is a strong driver of the photosynthetic decline during drought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 92 publications
6
108
0
Order By: Relevance
“…Here, stomatal conductance measured as the sum of both surfaces approached zero at −1.42 MPa. Studies on corn (Cochard, ), rice (Wang et al, ), and tomato (Skelton, Brodribb, & Choat, ) reported similar patterns of stomatal closure during dehydration suggesting that crops are sensitive to a changing environment and limit water losses early during water stress.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Here, stomatal conductance measured as the sum of both surfaces approached zero at −1.42 MPa. Studies on corn (Cochard, ), rice (Wang et al, ), and tomato (Skelton, Brodribb, & Choat, ) reported similar patterns of stomatal closure during dehydration suggesting that crops are sensitive to a changing environment and limit water losses early during water stress.…”
Section: Discussionmentioning
confidence: 93%
“…Xylem vulnerability to cavitation has been widely studied and provides a predictive indication of plant tolerance and mortality during drought (Anderegg et al, 2015). However, some studies report declines in K leaf at water potentials insufficient to cause cavitation but before or concomitant with stomatal closure (Brodribb & Holbrook, 2006;Holloway-Phillips & Brodribb, 2011;Scoffoni et al, 2018; Torres-Ruiz, Diaz-Espejo, Perez-Martin, & Hernandez-Santana, 2015;Wang, Du, Huang, Peng, & Xiong, 2018). One possible explanation for this behaviour is xylem wall implosion (i.e., xylem collapse) under negative pressure (Cochard, Froux, Mayr, & Coutand, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study performed by Wang et al . () reports simultaneously the dynamics of K leaf , g s and g m during a drought event, showing that K leaf is the main driver of g s and g m decline under water stress in rice. K leaf decline with water stress compromises water availability in leaves, thus contributing to the hydraulic‐driven decline in g s (Theroux‐Rancourt et al ., ) and possibly to reduced g m as well.…”
Section: Coupling Of Hydraulics and Photosynthesismentioning
confidence: 98%
“…normalAnormalNnormalCnormalc was calculated as the slope of A N /C c response curves over a C c range of 50 to 100 μmol mol −1 (Tomás et al ): dgsgs=normalgnormalsnormalrefnormalgnormals/normalgnormalsnormalref dgmgm=normalgnormalmnormalrefnormalgnormalm/normalgnormalmnormalref normaldjnormalj=normaljnormalmnormalrefj/normaljnormalmnormalref where normalgnormalsnormalref, normalgnormalmnormalref and normaljnormalmnormalref are the reference values of stomatal and mesophyll conductance and of electron transport rate, respectively. In the current study, the maximum g s , g m and J flu were generally reached under WW conditions, therefore the maximum value among the WW treatment was used as a reference (Flexas et al , Wang et al ).…”
Section: Methodsmentioning
confidence: 99%